ROOT CAUSES OF CYBERCRIME AMONG UNDERGRADUATES IN BENIN CITY - Ajayi, Ohiomah; Amorighoye, Deston Efejuku; Osayi, Maybell Igie (African Journal of Social and Behavioural Sciences, 2025)
This study investigated the root causes of cybercrime among undergraduates in Benin City, Nigeria. Using a quantitative research design, the study examined the relationships between economic necessity, cyber security awareness, and engagement of undergraduates in cybercrime. A total of 300 questionnaires were administered to selected respondents using the stratified random sampling technique. Simple percentages were used to analyse the demographic characteristics of the respondents, while chi-square analyses were used to analyse the data and test the hypotheses. The findings revealed a significant relationship between economic necessity and the involvement of ndergraduates in cybercrime (χ² = 12.96, p < 0.05). Additionally, the results showed a significant relationship between cyber security awareness and the vulnerability of undergraduates to cybercrime (χ² = 16.00, p < 0.05). The quantitative Findings showed that 60% of the respondents were males, while 40% were females. Also, 40% of the respondents were between 18-20 years, 30% were between 21-23 years, 15% were between 24-26 years, and 15% were between 27-30 years. The Chi-square analysis revealed a significant relationship between economic necessity and undergraduates’ engagement in cybercrime. The findings suggested that economic hardship drives undergraduates to engage in cybercrime as a means of survival. The Chi-square analysis also showed a significant relationship between cybersecurity awareness and the involvement of undergraduates in cybercrime using Chi-square analysis. The findings suggested that undergraduates who lacked cyber security awareness were more vulnerable to cybercrime. The study contributed to the understanding of the root causes of cybercrime among undergraduates in Benin City, Nigeria. It provided recommendations for policymakers, law enforcement agencies, and stakeholders seeking to combat cybercrime.